The Relationship Between CT Value and Clinical Degree of Children With Covid-19 in RSU Bunda Thamrin Medan - Siregar, Ifany Hafidzah; Airlangga, Eka (Buletin Farmatera, 2025)
Abtract : Coronavirus disease 2019 (COVID-19) is caused by Coronavirus 2 acute respiratory syndrome (SARS-CoV-2). COVID-19 has varied clinical manifestations, ranging from asymptomatic, mild, moderate, severe and critical. Diagnosis in COVID-19 patients can be established using RT-PCR. This study aims to determine the relationship between CT value and clinical degree of children with covid-19 in RSU Bunda Thamrin Medan.This type of research is an analytical observational study with a cross-sectional study. The number of samples in this study was 165 samples. Of the 165 pediatric patients diagnosed with COVID-19, 53 children (32.12%) were aged 5 years while 112 children (67.88%) were aged ≥ 5 years. Males were 97 children (58.79%) and girls were 68 (41.21%). The most common comorbid disease was obesity, which was 51 children (67.1%). Pediatric patients with asymptomatic symptoms 8 children (4.8%), 126 children (76.4%) with mild symptoms, 7 children (4.2%) with moderate symptoms, 23 children (13.9%) with severe symptoms and 1 child (0.6%) with critical symptoms. 143 children (86.67%) patients had CT Value values ≤ 29, 21 children (12.73%) patients with CT Value values of 30 – 37, and 1 child (0.6%) had CT Value values of 38 – 40.  In this study, it was found that there was a relationship between CT Value and the clinical degree of children with COVID-19.